A monograph and re-classification of the previous genus Limosina Macquart (Diptera, Sphaeroceridae) of Europe. Part III. - Roháček, Jindřich (Contributions to Entomology = Beiträge zur Entomologie, 1983)
The European species belonging to the previous genus Limosina Macquart (sensu Hackmann 1969a) are monographed. This taxon was found to be polyphyletic and is divided using cladistic classification into 17 genera with a total of 81 European species. 11 genera and 11 subgenera are discribed as new: Gigalimosina gen. nov., Herniosina gen. nov., Terrilimosina gen. nov., Minilimosina gen. nov., Minilimosina (Svarciella) subgen. nov., Minilimosina (Allolimosina) subgen. nov., Xenolimosina gen. nov., Paralimosina (Canarisina) subgen. nov., Spelobia (Eulimosina) subgen. nov., Spelobia (Bifronsina) subgen. nov., Pullimosina gen. nov., Pullimosina (Dahlimosina) subgen.nov., Spinilimosina gen. nov., Kimosina gen. nov., Kimosina (Kollimosina) subgen. nov., Kimosina (Alimosina) subgen. nov., Telomerina gen.nov., Opalimosina gen. nov., Opalimosina (Pappiella) subgen. nov., Opalimosina (Hakmanina) subgen. nov., Opalimosina (Dentilimosina) subgen. nov., and Rudolfia gen. nov. Other included (Limosina Maquart, 1835; Apteromyia Vimmer, 1929 gen. restit.; Paralimosina Papp, 1973; Spelobia Spuler, 1924 nom. restit., stat. nov.; Chaetopodella Duba, 1920; Halidayina Duba 1918) are rediscribed. Descriptions of 14 new species are given (Minilimosina 4, Spelobia 6, Kimosina 1, Telomeina 3), other are fully rediscribed. 4 new synonyms are established; numerous species (besides those included in the Monograph) are put in new combinations. All available type material of European species (including synonyms) was revised, number of lectotypes designated and in this way the status of particular species fixed. A description of each species is supplemented by numerous illustrations, data on the morphology of preimaginal stages, biology, distribution and by discussion of relationships. Identification keys to all included taxa are given. The general part includes a summary of basic data dealing with history of investigations, morphology, biology, zoogeography and phylogeny (cladistic classification) of the groups under study.